Political Psychology of Land Conflict and Peacebuilding in Central Mindanao: A Social Representations Approach - Galang, Adrianne John R. (Kasarinlan: Philippine Journal of Third World Studies; Vol 30, No 2-Vol 31, No 1 (2015-2016): Indigenous People and Contested Access to Land, 2017)
Book review of  Montiel, Cristina Jayme, Judith M. De Guzman, Marshaley J. Baquiano, and Audris P. Umel. 2013. Political Psychology of Land Conflict and Peacebuilding in Central Mindanao: A Social Representations Approach. Quezon City: Institute of Philippine Culture, School of Social Sciences, Ateneo de Manila University. 80 + x pp.